The Patterns Between 9th Grade Students’ Level of Subject Matter Knowledge and the Cognitive and Metacognitive Strategies They Use While Solving Multiple Choice Questions in Science - DİKEN, Emine Hatun and YÜRÜK, Nejla (Journal of Posthumanism, 2025)
This research aimed to explore the strategies employed by 9th-grade students from Science High Schools, Anatolian High Schools, and Vocational High Schools when solving multiple-choice science questions, examining how these strategies differed based on the students’ subject matter knowledge and the difficulty of the questions. These participating students solved multiple-choice science questions from the units of “Force and Motion, Structure and Properties of Substance, and Living Creatures and Energy Relations”. The students were observed by the researcher in the process of solving the questions, and students were asked to think aloud to determine the cognitive and metacognitive strategies used by the students. A qualitative case study approach was adopted, involving 15 students from these three school types in Ankara. Data were gathered through observation records of students’ question-solving processes and semi-structured interviews conducted after solving the questions. To determine students’ levels of content knowledge related to the multiple-choice questions, they were asked open-ended questions about each multiple-choice question. The results revealed that the subject matter knowledge of Science and Anatolian High School students played a crucial role in answering questions correctly, and the cognitive and metacognitive strategies they employed were essential for reaching accurate answers. Additionally, it was found that some students from these schools, despite using a variety of cognitive and metacognitive strategies, failed to answer correctly due to underlying misconceptions. In addition, it was found out that some students from the Science High School and Anatolian High Schools answering the questions wrongly had misconceptions despite using a large number and variety of cognitive and metacognitive strategies.